Applying the new guidelines to asthma management in children. Issue 2 (12th April 2023) - Castagnoli, Riccardo; Brambilla, Ilaria; Giudice, Michele Miraglia Del; Marseglia, Gian Luigi; Licari, Amelia
Abstract : Purpose of review: This review aims to provide paediatricians with novel concepts from scientific evidence applicable to treating children with asthma. The latest guideline updates on paediatric asthma are discussed here, with a focus on the 2022 update of the GINA document. Recent findings: Mild asthma remains to be an important challenge for the paediatrician, and the introduction of new evidence-based treatment strategies, particularly those symptom-driven, could have a significant impact on the paediatric population. The identification of predictive biomarkers, the definition of biological treatment response, the possible duration of these therapies in this age group, as well as their potential action on airway remodelling are desirable in the short term. As the number of available biological treatment options expands, paediatricians should be supported by further evidence in decision-making. Summary: There is an urgent need to implement at multiple levels the latest therapeutic strategies proposed for asthma at all severities.